Doing Digital Migration Studies: Theories and Practices of the Everyday - Leurs, Koen; Ponzanesi, Sandra (Media, Culture and Communication in Migrant Societies, 2024)
Doing Digital Migration present a comprehensive entry point to the variety of theoretical debates, methodological interventions, political discussions and ethical debates around migrant forms of belonging as articulated through digital practices. Digital technologies impact upon everyday migrant lives, while vice versa migrants play a key role in technological developments – be it when negotiating the communicative affordances of platforms and devices, as consumers of particular commercial services such as sending remittances, as platform gig workers or test cases for new advanced surveillance technologies. With its international scope, this anthology invites scholars to pluralize understandings of ‘the migrant’ and ‘the digital’. The anthology is organized in five different sections: Creative Practices; Digital Diasporas and Placemaking; Affect and Belonging; Visuality and digital media and Datafication, Infrastructuring, and Securitization. These sections are dedicated to emerging key topics and debates in digital migration studies, and sections are each introduced by international experts.